Séries iniciais: um panorama das pesquisas produzidas no Programa de Estudos Pós-Graduados em Educação Matemática da PUC/SP no período de 1994 a 2008 - Oliveira, Sandra Dourado de (2010)
This investigation had the purpose to accomplish a view of dissertations about the first series produced from 1994 to 2008, at PUC/SP, emphasizing, specially contents, methodologies and/or methodological proceedings and main results. The defined methodology has bibliographycal feature and, for the labours´ selection, it was utilized the site of the Postgraduate Studies Program in Mathematical Education, following a predetermined beginning, establishing in the total reading, fingerprinting and works analysis. The analysis of documents was established to locate, in dissertations, evidences of typical activities of search proposed by Romberg (1992). Then, the results have shown that the preference of the searches, was by contents explored in the classroom by the student view point among several, most searchers chose like theme numbers and operations. So, the similarities found, consist of methodology and/or methodological proceedings, main considerations and theoretical fundamentation by the psychology view. However, there were some divergences in the theoretical indicators related to the search theme. Besides, every authors were worried to create situations that helped the development of meanings to the Math contents chosen. At last, It´s considered that the search mentioned could provide assistance for future investigations